Meshless Radial Basis Function Pseudo-Spectral Method for Solving Non-linear KdV Equation - Dasari, Shrikrishna; Parikh, Amit (Communications in Mathematics and Applications, 2023)
The Korteweg-De Vries (KdV) problem is solved in this study using a meshless strategy based on the radial basis function. The nonlinear KdV equation is solved using the radial basis function in conjunction with the pseudo-spectral method. With the aid of a radial basis function, the method transforms the problem into a system of ODEs, which are subsequently solved by an ODE solver. The usefulness and efficiency of the strategy are assessed using two numerical examples. The numerical results are well-aligned with the exact solutions found in the literature.